Formation of hardened layer in WC-TiC-Co alloy by treatment of high intensity pulse ion beam and compression plasma flows; Surface and Coatings Technology; Vol. 204, iss. 12-13 - Uglov V. V. Vladimir Vasilievich; Remnev (Remnyov) G. E. Gennady Efimovich; Kuleshov A. K.; Astashinski V. M.; Saltymakov M. S. Maksim Sergeevich (2010, 2010)
Title screen